Homologous pairing of single-stranded DNA and superhelical double-stranded DNA catalyzed by RecO protein from Escherichia coli. - Luisi-DeLuca, C (1995)
The recO gene product is required for DNA repair and some types of homologous recombination in wild-type Escherichia coli cells. RecO protein has been previously purified and shown to bind to single- and double-stranded DNA and to promote the renaturation of complementary single-stranded DNA molecules. In this study, purified RecO protein was shown to catalyze the assimilation of single-stranded DNA into homologous superhelical double-stranded DNA, an activity also associated with RecA protein. The RecO protein-promoted strand assimilation reaction requires Mg2+ and is ATP independent. Because of the biochemical similarities between RecO and RecA proteins, the ability of RecO protein to substitute for RecA protein in DNA repair in vivo was also assessed in this study. The results show that overexpression of RecO protein partially suppressed the UV repair deficiency of a recA null mutant and support the hypothesis that RecO and RecA proteins are functionally similar with respect to strand assimilation and the ability to enhance UV survival. These results suggest that RecO and RecA proteins may have common functional properties.